Kinetics and Mechanism of Bromide Catalysed Oxidation of L-Sorbose by Cerium(IV) in Aqueous Sulphuric Acid Solution - Sah, M.P.; Jha, M.D.; Pathak, A.K.; Lal, K.B.; Sinha, S.K. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of L-sorbose has been studied in presence of bromide catalyst in aqueous sulphuric acid medium at constant ionic strength. The reaction is first order each in L-sorbose and [Ce(IV)]. The rate of reaction decreases on increasing the concentration of hydrogen ion. The sulphate and bisulphate ions show retarding effect on reaction rate at constant ionic strength. The bromide ion shows positive catalytic effect on reaction rate. The value of activation energy has been calculated and a suitable mechanism conforming to the kinetic data is proposed.